A desfeminização do magistério: uma análise da literatura pedagógica brasileira da segunda metade do século xx - Scherer, Renata Porcher (Universidade do Vale do Rio dos Sinos, 2019)
Understanding why the portraits of the Brazilian teaching continue to be constituted nowadays around the vocation and the maternity, sometimes around the technical and professional knowledge is a challenge that this Thesis assumes. When choosing Brazilian teaching as an object of research, from a historical perspective, the following questions are proposed: What practices and modifications can be described about Brazilian teaching in the Brazilian pedagogical literature of the second half of the twentieth century? In what ways does gender cross and scale these practices and modifications? To compose the empirical material, 9 (nine) books of the Brazilian pedagogical literature written from the 1960s to the 2000s were selected. The methodological procedure used is documentary research, assuming a perspective of looking at documents as monuments, anchored in the studies of two authors: Michel Foucault and Jacques Le Goff. This perspective of looking implies to analyze the documents from its exteriority, understanding the conditions of possibility for its creation. The concept of problematization is also used as a methodological assumption that allows to operate under the teaching problematic analyzing its practices and modifications in a determined period. The theoretical tool put into action to develop the analysis of the empirical material is the concept of gender, taking as main contribution the theoretical contributions of different authors that integrate the so-called field of poststructuralist gender studies: Joan Scott, Linda Nicholson, Dagmar Meyer, among others. Thus, in this thesis, three forms of problematization about Brazilian teaching were mapped, corresponding to specific historical periods: (1) in the 1960s a tension movement of the feminization process of the Brazilian teaching and the decline of the craft-missionary conception of Brazilian teaching; (2) in the 1980s a debate between political commitment and technical competence that criticized a teaching centered on the attributes of love and care; (3) in the 1990s, contemporary discussions about the role of teachers, a debate that opposes the notions of transmission and construction of knowledge and a radical questioning about the professionalization movement of the teaching profession. The conjunction of these three forms of problematization, in articulation with the conceptual tool gender, allows us to support the thesis that in the second half of the twentieth century the Brazilian teaching passed through a process of defeminization, where technical and professional knowledge were affirmed from a denial the absolutization of affection and an affirmation of political commitment. Therefore, the thesis of defeminization is not supported by a reduction of women in teaching, especially primary, but it seeks to show how the Brazilian pedagogical literature, by defending technical competence and political commitment, attempted to point to the importance of a teaching that did not have in its nature (do not carry itself) a female a priori.
Keywords: Docência; Gênero; Magistério brasileiro; Feminização do magistério; Literatura pedagógica; Teaching; Genre; Brazilian teaching; Feminization of teaching; Pedagogical literature; ACCNPQ::Ciências Humanas::Educação